2022
DOI: 10.3390/app121910170
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Retooling Humanities Courses: Finance and Marketing Experience at a Czech University

Abstract: Virtual reality environments (VRE) allow users to visualize both real-life and imaginary activities. For this reason, they make appropriate training fields at universities, too. However, the positive or negative effects of VRE are still a subject of research. There is a need to verify methods of their deployment, student responses and the impact of VRE implementation. Science and medicine courses are frequently exploiting VRE, while their exploitation in humanities is much less frequent. In our paper, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, technical issues or disadvantages still need to be addressed. For example, some technical difficulties may be experienced since VR-based courses' design, development and practice are time-consuming and costly (Koreňová et al, 2022). Besides, VR could isolate and distract users from the real world (Çoban et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, technical issues or disadvantages still need to be addressed. For example, some technical difficulties may be experienced since VR-based courses' design, development and practice are time-consuming and costly (Koreňová et al, 2022). Besides, VR could isolate and distract users from the real world (Çoban et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Students' comments on individual training courses' strengths and weaknesses help design visions for improvement. With regards to the visions of the students' feedback, the possibilities of improving could be necessary to research, e.g., including technical-based innovations [2] or analyses of the utilization of essential study materials [3]. Teachingquality assessment questionnaires are not new in tertiary education but have been used for more than 80 years, as older studies have shown [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to a consensus in the higher education environment, student feedback improves teaching and helps develop effective teaching strategies. Alternative methods for developing effective teaching strategies in the additional sense can be seen, e.g., in [1,2], as challenges within learning or including virtual reality (ICT methods). Aditomo and Kohler [7] state that teachers and their teaching strategies are the main factors that determine students' learning outcomes.…”
Section: Introductionmentioning
confidence: 99%